Time Management Among Students in Achieving Their Qur'an Memorization Goals at Islamic Boarding School - Aulia Nabila; Afiful Ikhwan; Devid Dwi Erwahyudin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines the time management of students in achieving their Quran memorization targets at the Ar-Rohmah Islamic Boarding School, Tahfidz Unit, Ngawi. Tahfidz students face dual challenges: the obligation to memorize new verses (ziyadah), review previously memorized verses (muroja’ah), participate in formal classroom instruction, and adhere to the boarding school’s daily routine. This study aims to explain the boarding school’s strategies in helping students manage their time and to analyze the impact of these strategies on the achievement of memorization targets. A qualitative approach with a case study design was employed, involving female students actively enrolled in the tahfidz program (intermediate and advanced levels) as the primary subjects. Data were collected through participant observation, in-depth interviews, and documentation, and subsequently analyzed using the Miles & Huberman interactive model. The research findings indicate that Ar Rohmah Islamic Boarding School implements a structured time management system with three daily recitation sessions: review of previously memorized verses after dawn prayer (minimum 5 pages), review of new verses from 7:00–8:00 AM, and ziyadah (new memorization) after afternoon prayer. This strategy is supported by the use of Arabic as the daily language, guidance from halaqah supervisors, as well as weekly and monthly recitation sessions. The resulting impacts include the achievement of the memorization target of 5 juz per year, measurable fluency in recitation, and improvements in the quality of tajwid and fashah. This study contributes to the development of a schedule-routine model for time management in Al-Qur’an memorization institutions.